Assessing the Permanence of Land Use Change Induced by Payments for Environmental Services Evidence from Nicaragua - Pagiola, Stefano (The World Bank, 2017)
There have been few efforts to evaluate whether the positive land use changes induced by conservation interventions such as Payments for Environmental Services (PES) persist once the interventions end. Since gains achieved by conservation interventions may be lost upon termination of the program, even apparently successful interventions may not result in longterm conservation benefits, a problem known as that of permanence. This paper examines the permanence of land use changes induced by a short-term PES program implemented between 2003 and 2008 in Matiguas-Rio Blanco, Nicaragua. This PES program had been found to have a positive and highly significant impact on land use, and particularly on the adoption of silvopastoral practices. To assess the long-term permanence of these changes, participants were re-surveyed in 2012, four years after the last payment was made. We find that the land use changes that had been induced by PES were broadly sustained in intervening years, with minor differences across specific practices and sub-groups of participants. The patterns of change in the period after the PES program was completed help us understand the reasons for the program's success, and rule out alternative explanations for the program's success. Our results suggest that, at least in the case of productive land uses such as silvopastoral practices, PES programs can be effective at encouraging land owners to adopt environmentally beneficial land use practices and that the benefit will persist after payments cease